Clinical features of the arterial hypertension in a medical emergency service in Abidjan - Diallo, A D; Mouanodji, M B; Niamkey, E K; Yao, B B (African Journal of Nephrology, 2016)
The authors studied the clinical features of high hypertension (blood pressure over 240 mmHg for the systolic and over 140 mmHg for the diastolic pressure) in 300 black African patients observed in the unit of medical emergency at Abidjan. In this unit arterial hypertension represented 8.27% of the cases and was the main cause of mortality (12.9 % VS 7.2 % for the others causes). The common complications were heart failure (29%), stroke (21 %), encephalopathy (19%) and renal failure (16%). Diabetes was associated in 8.33% of cases. The high rate of mortality is observed when there was stroke (25.4%) and renal fai lure (25%). There was significant increase in mortality linked to high blood pressure.